2017
DOI: 10.5830/cvja-2016-055
|View full text |Cite
|
Sign up to set email alerts
|

Adropin as a potential marker of enzyme-positive acute coronary syndrome

Abstract: SummaryAimEnzyme-positive acute coronary syndrome (EPACS) can cause injury to or death of the heart muscle owing to prolonged ischaemia. Recent research has indicated that in addition to liver and brain cells, cardiomyocytes also produce adropin. We hypothesised that adropin is released into the bloodstream during myocardial injury caused by acute coronary syndrome (ACS), so serum and saliva levels rise as the myocytes die. Therefore, it could be useful to investigate how ACS affects the timing and significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Adropin levels in saliva and serum samples were identified as diagnostic biomarkers of enzymepositive acute coronary syndrome (EPACS), with adropin levels starting to decrease at 6 h after EPACS. 45 A previous study of 82 patients revealed that serum adropin levels were reduced in patients with angiographically confirmed coronary slow flow phenomenon (CSFP). 46 Serum adropin concentrations were inversely correlated with AF and atrial remodelling.…”
Section: Adropin Regulates Biological Pathways That Are Directly Ormentioning
confidence: 99%
See 1 more Smart Citation
“…Adropin levels in saliva and serum samples were identified as diagnostic biomarkers of enzymepositive acute coronary syndrome (EPACS), with adropin levels starting to decrease at 6 h after EPACS. 45 A previous study of 82 patients revealed that serum adropin levels were reduced in patients with angiographically confirmed coronary slow flow phenomenon (CSFP). 46 Serum adropin concentrations were inversely correlated with AF and atrial remodelling.…”
Section: Adropin Regulates Biological Pathways That Are Directly Ormentioning
confidence: 99%
“…Low adropin was also found to be an independent risk factor for cardiac syndrome X (also known as microvascular angina). Adropin levels in saliva and serum samples were identified as diagnostic biomarkers of enzyme‐positive acute coronary syndrome (EPACS), with adropin levels starting to decrease at 6 h after EPACS 45 . A previous study of 82 patients revealed that serum adropin levels were reduced in patients with angiographically confirmed coronary slow flow phenomenon (CSFP) 46 .…”
Section: Adropin Regulates Biological Pathways That Are Directly or Imentioning
confidence: 99%
“…It was also found that low serum adropin concentrations were an independent predictor for a high SYNTAX score ( Ertem et al, 2017 ). Additionally, in patients with enzyme-positive acute coronary syndrome (EPACS), significant increases in serum and salivary adropin levels were observed up to 6 h after the event and then began to decline ( Aydin et al, 2017 ). Based on the above results, it can be assumed that the measurement of adropin concentration in serum and saliva samples may be a new potential marker for diagnosing EPACS ( Aydin et al, 2017 ).…”
Section: Adropinmentioning
confidence: 99%
“…Additionally, in patients with enzyme-positive acute coronary syndrome (EPACS), significant increases in serum and salivary adropin levels were observed up to 6 h after the event and then began to decline ( Aydin et al, 2017 ). Based on the above results, it can be assumed that the measurement of adropin concentration in serum and saliva samples may be a new potential marker for diagnosing EPACS ( Aydin et al, 2017 ). Furthermore, there is evidence that low adropin serum may be a prognostic marker for stable CAD (SCAD) and the severity of coronary arteriosclerosis ( Zhao et al, 2015 ).…”
Section: Adropinmentioning
confidence: 99%
“…It is a small polypeptide essentially play an important role in in ammation and some metabolic events [6]. Few studies have suggested the use of adropin as a biomarker in patients suffering from conditions with cellular hypoxia and destruction, such as acute myocardial infarction [7,8].…”
Section: Introductionmentioning
confidence: 99%